Pemanfaatan Layanan Koleksi Digital Di Upt Perpustakaan Universitas Negeri Padang Menggunakan Model Eucs (End User Computing Satisfaction) - Wati Khotimah, Fatma; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2022)
This study aims to describe the use of digital collection services at the Padang State University Library UPT using the EUCS (End User Computing Satisfaction) model. This study uses a quantitative type with a descriptive method. The population in this study is the average number of visitors who come to the digital collection service at the Padang State University Library from January to December 2021 totaling 3,112 members with a sample of 97 people. Sampling was determined based on a simple random sampling technique, namely a random sampling technique without regard to the existing strata in the population. The results of this study are the use of digital collection services at the Padang State University Library UPT using the EUCS (End User Computing satisfaction) model with 5 dimensions with an average score of 3.19. The content dimension obtained an average score of 3.26 which is on a positive interval scale, namely there is user satisfaction because digital collection services provide information according to user needs and have complete information. The accuracy dimension obtained an average score of 3.11 which is on a positive interval scale, namely there is user satisfaction because the information generated by digital collection services is accurate. The format dimension obtained an average score of 3.14 is on a positive interval scale, namely there is user satisfaction. The aesthetic/beauty side of the interface contained in the digital collection service system has an effect on both the search and the information displayed in PDF form. The ease of use dimension obtained an average score of 3.19 on a positive interval scale. There is user satisfaction due to the ease of users in accessing information, clarity of instructions in accessing information on digital collection services, adequacy of computers and users finding information with the keywords used. The timeliness dimension obtained an average score of 3.23 which is on a positive interval scale, namely there is user satisfaction because digital services provide the latest information provided on digital services and the desired information.